Rents, dissipation and lost treasures: comment - Johannes Münster (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In an interesting recent paper, Dari-Mattiacci and Parisi (2005) extended Tullock.s (1980) rent-seeking game with an entry decision. The mixed strategies identified by Dari-Mattiacci and Parisi for the case of increasing returns in the contest success function (r > 2) do not constitute an equilibrium of the game they study. However, these strategies are an equilibrium if the strategy space of the game is restricted by a minimum expenditure requirement, and this minimum expenditure requirement is an element of a specific interval.
urn:nbn:de:bvb:19-epub-13432-9
Keywords: 330